Conditional Control of CRISPR/Cas9 Function by Chemically Modified Oligonucleotides - Liangliang Wang; Yan Liu; Hongjun Song; Xue Zhang; Yang Wang (Molecules)
The CRISPR (clustered regularly interspaced short palindromic repeats) system has emerged as a revolutionary gene-editing tool with immense potential in gene therapy, functional genomics, and beyond. However, achieving precise spatiotemporal control of gene editing in specific cells and tissues while effectively mitigating potential risks, such as off-target effects, remains a key challenge for its clinical translation. To overcome these limitations, researchers have developed innovative strategies based on chemical modifications of oligonucleotides to enhance the precision, efficiency, and controllability of CRISPR/Cas9-mediated gene editing. By introducing conditional responsive elements, such as photosensitive groups, small-molecule responsive units, and supramolecular structures, they have successfully achieved precise spatiotemporal and dose-dependent regulation of CRISPR/Cas9 function. This review provides a comprehensive overview of recent advancements in gRNA regulation strategies based on chemical modifications of oligonucleotides, discussing their applications in improving the efficiency, specificity, and controllability of CRISPR/Cas9 editing. We also highlight the challenges associated with the conditional control of gRNA and offer insights into future directions for the chemical regulation of gRNA to further advance CRISPR/Cas9 technology.